EFEKTIVITAS PENYALURAN KREDIT USAHA RAKYAT DI BANK SULAWESI UTARA DAN GORONTALO CABANG RATAHAN KABUPATEN MINAHASA TENGGARA - Marsela Gonta; Arie Rorong; Very Londa (JURNAL ADMINISTRASI PUBLIK, 2023)
ABSTRACTThis research was conducted with the aim of examining the effectiveness of distributing Kredit Usaha Rakyat at the North Sulawesi and Gorontalo Bank (BSG) Ratahan branch, Southeast Minahasa Regency. The method used in this study is qualitative research where data is collected based on conditions that occur in the field which are then described. Data collection was carried out through three data collection techniques, namely observation, interviews and literature study. The results of this study found that KUR distribution at the BSG Ratahan branch was based on four Budiani indicators, namely accurancy of target program, socialization of program,objectives of program and supervision of program. This research suggests that the BSG Ratahan branch conduct more frequent supervision regarding customers and also strengthen relationships with customers through clear communication and information regarding monthly payments, as well as KUR debtors to be wiser in using KUR assistance.